1988
DOI: 10.1056/nejm198808113190603
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Year Follow-up of Survival in the Randomized European Coronary Surgery Study

Abstract: We studied survival rates among 767 men with good left ventricular function who participated in the European Coronary Surgery Study, 10 to 12 years after they were randomly assigned to either early coronary bypass surgery or medical therapy. At the projected five-year follow-up interval, we observed a significantly higher survival rate (+/- 95 percent confidence interval) in the group that was assigned to surgical treatment than in the group assigned to medical treatment (92.4 +/- 2.7 vs. 83.1 +/- 3.9 percent;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
190
0
17

Year Published

1989
1989
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 636 publications
(209 citation statements)
references
References 18 publications
2
190
0
17
Order By: Relevance
“…23 Following these sub-analyses, the subgroup with p-LAD involvement (> = 50% stenosis) and presence of 2-vessel or 3-vessel CAD was evaluated. 19 This analysis revealed that CABGS, compared to medical therapy, was associated with a significantly lower mortality rate. On the basis of this subanalysis, 19 patients with p-LAD involvement were identified as a high-risk subgroup that appeared to derive benefit from therapy with CABGS.…”
Section: Comparison Of Myocardial Revascularization With Medical Therapymentioning
confidence: 93%
See 4 more Smart Citations
“…23 Following these sub-analyses, the subgroup with p-LAD involvement (> = 50% stenosis) and presence of 2-vessel or 3-vessel CAD was evaluated. 19 This analysis revealed that CABGS, compared to medical therapy, was associated with a significantly lower mortality rate. On the basis of this subanalysis, 19 patients with p-LAD involvement were identified as a high-risk subgroup that appeared to derive benefit from therapy with CABGS.…”
Section: Comparison Of Myocardial Revascularization With Medical Therapymentioning
confidence: 93%
“…The VACSS 12,13 included patients with left main coronary (LMC) artery involvement; LMC + (abnormal left ventricular function (LVF) or normal LVF); no-LMC, 2v + abnormal LVF; 3v + abnormal LVF; 1v, 2v, 3v, impaired LVF, nonimpaired LVF; high angiographic risk (3v + impaired LVF); and low angiographic risk ( Using an intention to treat (ITT) analysis approach the VACSS, ECSS, and CASS trials revealed similar mortality rates between the main CABGS and medical therapy arms. 14,19,26,27 The ECSS is the only trial that showed on long-term follow-up a small, but statistically significant, improvement in mortality rate with CABGS. 19 The rates of fatal and nonfatal MI) in these trials were similar between the patients who underwent CABGS, compared to patient who did not undergo CABGS.…”
Section: Comparison Of Myocardial Revascularization With Medical Therapymentioning
confidence: 99%
See 3 more Smart Citations